Improving rheological and filtration properties of water based drilling fluid using palm derived methyl ester sulphonate surfactant and waste polystyrene nano-particle - Sia, Luke Kennedy Si Lung (Curtin University, 2018)
A new mud was formulated to improve the drilling efficiency under HPHT condition using green surfactant and nano-polystyrene. A series of rheological and filtration tests were done to ensure that the mud can maintain its integrity once used in ultra-deep wells. Scanning electron microscope based image analysis was done to evaluate the plugging abilities of nanopolystyrene. It was found that the nano-polystyrene is able to improve the performance of the mud under different conditions.